Anisotropic fractional viscoelastic constitutive models for human descending thoracic aortas. (November 2019) - Amabili, Marco; Balasubramanian, Prabakaran; Breslavsky, Ivan
Abstract: The generalized fractional Maxwell model, formulated for hyperelastic material within the framework of the nonlinear viscoelasticity with internal variables, is applied to identify viscoelastic constitutive equations from layer-specific experimental data obtained by uniaxial harmonic loading of ex-vivo human descending thoracic aortas. The constitutive parameters are identified by using a genetic algorithm for the optimal fitting of the experimental data. The accuracy of the fitted fractional model is compared to the fitted integer order model with the same number of Maxwell elements. The formulation of an original strain energy density function for anisotropic nonlinear viscoelasticity is introduced and constitutive parameters are obtained from the experiments.